2019
DOI: 10.1590/1980-57642018dn13-040011
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance of children with spinal muscular atrophy: A systematic review

Abstract: Spinal muscular atrophy (SMA) is genetic and progressive, caused by large bi-allelic deletions in the SMN1 gene, or the association of a large deletion and a null variant. Objective: To evaluate the evidence about cognitive outcomes in spinal muscular atrophy (SMA). Methods: Searches on the PUBMED/Medline, Web of Knowledge and Scielo databases retrieved 26 studies (1989 to 2019, descriptors “spinal muscular atrophy” and “cognition”). Nine studies were selected according to the eligibility criteria: (1) cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 22 publications
(89 reference statements)
0
12
0
2
Order By: Relevance
“…This study reported a possible adaptive mechanism of an inverse correlation between executive function and physical ability, but the level of executive function did not exceed healthy controls (116). In contrast, there are indications of attention and executive function deficits in children with type I SMA (120,126).…”
Section: Spinal Muscular Atrophymentioning
confidence: 52%
See 1 more Smart Citation
“…This study reported a possible adaptive mechanism of an inverse correlation between executive function and physical ability, but the level of executive function did not exceed healthy controls (116). In contrast, there are indications of attention and executive function deficits in children with type I SMA (120,126).…”
Section: Spinal Muscular Atrophymentioning
confidence: 52%
“…For the most part, neuropsychological studies demonstrate preserved cognition (116)(117)(118)(119). This is with the caveat that these studies are mostly limited to children and omit the more severe clinical phenotypes (120). Some aspects of childhood development are even deemed superior compared to healthy controls (121)(122)(123)(124)(125).…”
Section: Spinal Muscular Atrophymentioning
confidence: 99%
“…Moreover, the increase in muscle strength promotes the worsening of contractures, therefore intensive stretching and the use of standing frame or knee-ankle-foot-orthoses when possible have to be envisaged. The reported cognitive involvement might be more frequent in longer-surviving SMA type I patients and this aspect has to be elucidated in long term follow-up [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recently published study focuses on the cognitive performance of adult SMA patients compared to patients suffering from ALS [ 32 ]. In previous studies, cognitive performance of children with SMA varies from average [ 21 , 33 ], above-average [ 18 ], and below-average [ 19 , 20 , 22 ]. In a study by Rivière et al spatial cognition was in the normal range in patients with SMA type 2 compared to healthy children [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians have noted their keen interest in their surroundings, their mental acuity, and their observational abilities in relation to the very pronounced physical limitations [ 17 , 18 ]. It was speculated whether the development of knowledge and cognitive skills might be a creative method of compensating for their many restrictions [ 18 , 19 ]. Based on patient’s reports with SMA type 2 and 3, it is assumed that they might focus on different physical activities during their leisure time compared to patients without physical disability [ 17 , 18 ] for example reading books or listen to music instead of sports or physical activity.…”
Section: Introductionmentioning
confidence: 99%